Results of major and trace element analysis of the glass shards from sediment core M1-A - Ivan Razum; Slobodan Miko; Nikolina Ilijanić; Maurizio Petrelli; Ursula Röhl; Ozren Hasan; Biagio Giaccio (PANGAEA, 2020)
Core M1-Afrom Mljet Island, Croatia, was retrieved from a submerged sinkhole to investigate tephra and reconstruct past sea levels. Eleven tephra layers were found, out of which six are macroscopically visible, while five are cryptotephra. For two of the tephra layers, glass shard concentrations were below the critical amount necessary for reliable analysis, while two more originated from a stratigraphical interval likely disturbed by drilling operations. Major and trace element compositions of glass shards were determined by wavelength dispersive spectroscopy(WDS) using an electron microprobe analyser (EMPA) and by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The tephra discrimination relied on a novel approach based on a multivariate analysis of element selection and the use of log-ratio scatterplots and common bivariate plots. The results enabled correlation of five tephra to known eruptions originating from Somma-Vesuvius and Campi Flegrei. Specifically,we identified Avellino Pumice, Mercato, Agnano Monte Spina and Neapolitan Yellow Tuff, extending known distributions for Avellino and Agnano Monte Spina. Moreover, our findings possibly support an earlier proposition that Agnano Monte Spina tephra originated from two eruptions with a pause of a few decades in between. Based on the tephra correlations and radiocarbon dating, an age-depth model was compiled that provided chronological constraints for the sea level during the formation of the lake (10.7 cal. ka BP, 49 m b.s.l.) and sea intrusion (2.3 cal. ka BP, 2.5 m b.s.l.).